Advances in Deterministic and Stochastic Analysis - Chuong, N. M. (Nguyen Minh) (World Scientific, 2007)
This volume collects articles in pure and applied analysis, partial differential equations, geometric analysis and stochastic and infinite-dimensional analysis. In particular, the contributors discuss integral and pseudo-differential operators, which play an important role in partial differential equations. Other methods of solving the partial differential equations are considered, such as the min-max approach to variational problems and boundary value problems. The foundations of quantum mechanics from the viewpoints of infinite-dimensional spaces and Bell's inequality and contraction are als.